PENGARUH KEPUASAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DI SENTRA INDUSTRI KULIT SUKAREGANG - Emron Edison; Titing Kartika; Rida Intan Dwi Lestari (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
The research was conducted at Sukaregang Leather Industry Center, Garut Regency. The descriptive research results show that job satisfaction, competence and performance are all in the category of "good." While the results of verifikatif analysis shows the effect of job satisfaction (X1) on employee performance (Y) of 11.70%, and with a ttest of 2.713> ttable 1.67 with significance 0.008 <0.050, this shows partially (ttest) has a positive and significant effect on employee performance. As for the competence variable (X2) has an effect on employee performance (Y) of 44.49%, and ttest of 7.700> ttable 1.67 with significance 0,000 <0,050, which means partial competence (ttest) has a positive and significant effect on employee performance. Simultaneously, it was found out that the effect of job satisfaction (X1) and competence (X2) on employee performance (Y) had total influence (R2 ) of 56.10%, the rest of 44% was un-researched variable, with Ftest> FTable 3, 94 with significance 0,000 <0,050, this indicates that job satisfaction and competence simultaneously (Ftest) have positive and significant influence on employee performance. As the overall research result shows that hypothesis statement is proven